2020
DOI: 10.3390/nu12051428
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Short Message Service Intervention on Excessive Gestational Weight Gain in a Low-Income Population: A Randomized Controlled Trial

Abstract: Objectives: The objective of this trial was to investigate the effect of educational short message service (SMS), or text messages, on excessive gestational weight gain (GWG) in a low-income, predominantly overweight/obese population. Methods: Participants (n = 83) were mostly overweight/obese women recruited at Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) clinics on the island of O’ahu, Hawai’i at 15–20 weeks gestational age. The intervention group received SMS on nutrition an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
(37 reference statements)
0
8
1
Order By: Relevance
“…This is in contrast to previous studies that have shown ineffective outcomes, particularly those focusing on online dietary interventions [ 10 , 11 , 12 , 13 , 14 ], which mainly provide static text or video information with limited incorporation of interactive information consultations or regular text responses. However, the acquisition of dietary information does not inherently impart healthy dietary knowledge and skills.…”
Section: Introductioncontrasting
confidence: 73%
See 1 more Smart Citation
“…This is in contrast to previous studies that have shown ineffective outcomes, particularly those focusing on online dietary interventions [ 10 , 11 , 12 , 13 , 14 ], which mainly provide static text or video information with limited incorporation of interactive information consultations or regular text responses. However, the acquisition of dietary information does not inherently impart healthy dietary knowledge and skills.…”
Section: Introductioncontrasting
confidence: 73%
“…Therefore, promoting dietary behaviors during pregnancy becomes crucial for enhancing the health of pregnant women. However, over time, many studies on dietary interventions during pregnancy have yielded mixed results, particularly a significant portion of online dietary intervention studies show no effect [ 10 , 11 , 12 , 13 , 14 ]. This may be related to insufficient key components in the intervention design, which may not have effectively addressed the critical barriers in pregnant women’s health dietary practices [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only three of the 15 included articles were qualitative studies Tinius et al, 2021). Among the quantitative papers, 11 were RCTs (Ainscough et al, 2020;Dodd et al, 2018;Ferrara et al, 2020;Gonzalez-Plaza et al, 2022;Henriksson et al, 2022;Holmes et al, 2020;Mackeen et al, 2022;Olson et al, 2018;Van Horn et al, 2018;Zhou et al, 2020). Our review revealed a cohort study assessing an intervention promoting healthy nutrition, physical activity, and gestational weight gain (GWG).…”
Section: Resultsmentioning
confidence: 99%
“…Women who received this behavioral therapy intervention gained less weight than women who did not (8.7 kg vs 12.3 kg; adjusted mean difference, −3.1 kg; 95% CI, −6.2 to −0.1), and the number of women who gained excessive weight in the intervention group was lower than that of women in the control group (37% vs 66%, P = 0.033) 47 . In contrast, a study of mostly overweight and obese women in Hawaii in which the intervention group received text messages concerning diet quality and quantity and exercise recommendations found no significant difference in GWG or the proportion with excess GWG, suggesting that the use of text messages may not be an effective intervention treatment, or the frequency of text messages may need to increase to be more effective 62 . Another Internet/smart phone–based intervention using a weight gain tracker and dietary and exercise tools to set and monitor goals found no effect 63 .…”
Section: Technologymentioning
confidence: 90%
“…47 In contrast, a study of mostly overweight and obese women in Hawaii in which the intervention group received text messages concerning diet quality and quantity and exercise recommendations found no significant difference in GWG or the proportion with excess GWG, suggesting that the use of text messages may not be an effective intervention treatment, or the frequency of text messages may need to increase to be more effective. 62 Another Internet/smart phone-based intervention using a weight gain tracker and dietary and exercise tools to set and monitor goals found no effect. 63 A small study (n = 54) tested in-person versus Internet/smart phone counseling and reported that both equally lowered the proportion of women with excess GWG compared with the control group.…”
Section: Technologymentioning
confidence: 99%